GMP compliant simplified fast and high yielding automated synthesis of [18F]fallypride without the need of HPLC purification - Ammar Alfteimi; Yi Zhao; Ulf Lützen; Alexander Helm; Michael Jüptner; Maaz Zuhayra (EJNMMI Radiopharmacy and Chemistry)
Abstract Background [18F]Fallypride PET has been used to study D2/3 receptor occupancy and density in neuropsychiatric disorders including Huntington’s disease (HD) and aging in humans. Nevertheless, the various synthetic methods including those provided by commercial synthesizers for [18F]fallypride exhibit a disadvantage concerning the necessity of using a HPLC purification step, which causes difficulties in the automation, leads to long synthesis times and moderate yields. Therefore utilizing the purification step by SPE cartridges is considered highly desirable for future commercialization of radiopharmaceutical cassettes. In our lab we have developed a simplified reliable automatic Radiosynthesis of [18F]fallypride by using SPE cartridges for the purification step without the need of HPLC. Results A simplified Radiosynthesis of [18F]fallypride has been developed without the use of HPLC for both a commercial cassette based synthesis system (AllinOne (AiO) system, Trasis, Belgium) and a research synthesis module with fixed tubing (RNplus, Synthra, Germany). The cleaning step involves a serial combination of several SPE cartridges. The synthesis time was shortened by 44% compared to synthesis using HPLC. At the same time the not decay corrected yield increases from 44 to 59% by using TBAHCO3 as phase transfer catalysts and from 17 to 31% for the synthesis with K2CO3/Kryptofix-[2.2.2] compared to synthesis using HPLC. The Radiochemical purity was always > 98% and all quality control parameters (e.g. sterility, endotoxin, stability and Radiochemical purity) conformed with requirements of the European Pharmacopoeia. Conclusions A GMP compliant automatic synthesis of [18F]fallypride including purification using simple solid phase extraction cartridges instead of HPLC was developed and evaluated. The implementation of the simplified synthesis in both used commercial modules allows efficient and reproducible Radiosynthesis of [18F]fallypride and leads to short synthesis times and high radiochemical yields with high radiochemical purity.